Kinetic study of inelastic radiation-induced processes in rare-gas cryocrystals: Electronic Processes in Cryocrystals - Ogurtsov, A.N.; Masalitina, N.Yu.; Bliznjuk, O.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
The processes of large-scale atomic displacements induced by exciton self-trapping were studied using the selective vacuum ultraviolet luminescence method. Models of Frenkel pairs creation in rare-gas crystals are discussed with a focus on excited-state mechanisms of defect formation. A simple kinetic model of defect accumulation in rare-gas samples is proposed.